STUDI KELAYAKAN PEMBUKAAN PROGRAM STUDI TADRIS IPA DI IAIN MADURA - Siti Azizah; Najwa Muqoddas; Dewi Nafila; Rabbianty, Eva Nikmatul (AS-SALAM, 2023)
With the increasing demand for science teachers in Pamekasan and the positive community response to the opening of a new study program, this research was conducted to evaluate the potential establishment of the Tadris IPA Study Program at IAIN Madura. Data was collected through questionnaires distributed to twelfth-grade students of SMA/SMK/MA in Pamekasan, Sampang, and Sumenep, as well as interviews with teachers, school principals, and the curriculum development team at IAIN Madura. As many as 78% of respondents supported opening the Tadris IPA Study Program, with 65% of prospective students expressing interest. About 70% of stakeholders hoped that graduates could integrate science and Islamic values. Based on the positive response from the community, the high interest from prospective students, and the expected graduate competencies, it is recommended that IAIN Madura consider opening the Tadris IPA Study Program. Integrating science and Islamic values is expected to meet the educational needs of Madura. Based on the data collected and the analysis conducted, the Tadris IPA Study Program at IAIN Madura is deemed worthy of establishment with specific considerations, including ensuring a qualified curriculum and a transparent faculty recruitment process.